Influence of floating electrode in gap breakdown with special attention to lightning side flashes - Nourirad, Ghasem (2014)
The influence of the presence of metallic parts on the body on the probability of lightning strikes to a human being is a long debated phenomenon without any concrete conclusions. There are many reported lightning incidents in publications and news in which victim stood nearby a place that has been struck by lightning. The two schools of thoughts that argue on both sides of the phenomenon mostly concentrate on direct lightning strikes. The percentage of side flashing injuries is four times more than that of direct strike. Some real events of lightning incidents have been reported in the dissertation in which there was a metallic object in vicinity that acted as a floating object. Consequently, the minimum separation between a human without having a floating electrode and an object which has been struck by lightning has been simulated and compared with the previous values. Then, the influence of the floating electrode carrying on the body or nearby is studied. An experimental setup has been done in UPM, UTM and TNBR to conduct the study. A rod-rod gap of 30 cm length has been implemented. Some different floating electrodes have been located between the two rods. Positive impulse is applied to one rod and the other rod is grounded. The test has been done for some specific positions of the floating electrodes to find out the influence of the floating electrode position. In each test, 25 shots have been attempted in the up and down procedure.Statistical analysis has been done using SPSS software to find the statistical significant differences of comparing two or more groups of obtained experimental data. Several modules have been used due to different tasks. The modules that have been used are Paired t-test, Independent t-test and Non-parametric test. The experimental results that are presented in this thesis show that there is a statistically significant influence of floating electrodes on rod-rod air gap breakdown when the floating electrode is close to either of the electrodes. The results may be extrapolated to explain the influence of electrical floating metal parts in lightning side flashes, where the arcing distances are a matter of only few meters. The theoretical results of calculation of minimum separation between a human and different objects stuck by lightning show that, the minimum separation depends on several parameters such as object impedance and lightning current parameters. In addition, the experimental outcomes are still inconclusive with regard to direct lightning strikes where the final jump may be few hundreds of meters. Based on our results we recommend the removal of metal parts from the body, if such action is possible, in the event of thunderstorms, especially when the person is within the proximity of potential objects for lightning strikes.